Anesthesia management for elective surgery in a patient with hereditary angioedema - Conceição, Luís; Martinho, Hélder; Azenha, Marta (Journal of the Portuguese Society of Anesthesiology, 2014)
The hereditary angioedema is an uncommon disease with dominant autossomic transmission, caused by a C1 inhibitor deficiency. This causes an uncontrolled activation of the classic pathway of the complement and of the cascade of kinins, being implicated in episodes of angioedema with possible involvement of the superior airways. The authors describe the anesthetic management of a 36 year old patient diagnosed with hereditary angioedema type I submitted to a general anesthesia for an elective cholecystectomy. Some preventive measures like the preoperative administration of 1000 units of C1 inhibitor concentrate were taken to avoid the angioedema of the airways. The authors briefly expose the pathophysiology, clinical manifestations and the anesthetic implications in the management of patients with this pathology.